A Roadmap for Future Development of Leadership Comptencies of ABC Non-Profit Organization , Thailand and Myanmar - Nang Bawk; Sirichai Preudhikulpradab (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This mixed-method research has two objectives: 1). identify current and preferred leadership competencies of all employees’ levels and rank the priority needs, 2). design a roadmap for the future development of ABC Organization, Thailand, and Myanmar’s leadership competencies. The instruments used comprise the structured questionnaire (n=64) and in-depth interview(n=10). The target populations comprise all employees, middle-level management, and top-level management, the purposive sampling method. The data analysis treatments include descriptive statistics and PNIModified for the structured questionnaire and contents analysis for the interview. Findings showed that the top three leadership competencies development per the ranking of priority needs comprised the Knowledge Competency (PNIModified=0.36), the Visionary Competency (PNIModified=0.34), the Communication Competency (PNIModified=0.26), and the Intrapersonal Competency (PNIModified=0.26). The recommendations are 1). The ABC organization focuses on the five competencies factors while activating succession planning and development to improve the employees’ leadership competencies–knowledge, visionary, communication, intrapersonal, interpersonal, and 2. A future study on identifying how to bridge the gap between top and middle management’s leadership competencies in ABC and formulate an additional proposal on a succession planning program.